Optical communication-based identification for multi-UAV systems: theory and practice - Bonilla Licea, Daniel; Walter, Viktor; Ghogho, Mounir; Saska, Martin (Autonomous robots, 2025)
Mutual relative localization and identification are important features for multi-unmanned aerial vehicle (UAV) systems. Camera-based communications technology, also known as optical camera communications in the literature, is a novel technology that brings a valuable solution to this task. In such a system, the UAVs are equipped with LEDs acting as beacons, and with cameras to locate the LEDs of the other UAVs. Specific blinking sequences are assigned to the LEDs of each of the UAVs to uniquely identify them. This camera-based system is immune to radio frequency electromagnetic interference and operates in global navigation satellite-denied environments. In addition, the implementation of this system is inexpensive. In this article, we study in detail the capacity of this system and its limitations. Furthermore, we show how to construct blinking sequences for UAV LEDs to improve system performance. Finally, experimental results are presented to corroborate the analytical derivations.